Wave diﬀraction and independent radiation by a buoyant body in ﬁnite-depth water by using an exact NtD boundary condition - Rim, Un-Ryong; Ko, Hyo-Song; Ri, Gum-Chon (Institut Teknologi Sepuluh Nopember, 2025)
Hydrodynamics of a ﬂoating structure is of interest from oﬀshore and coastal engineers who develop the wave energy converters and utilize the marine space resources. Recently, Rim [1-3] proposed an exact DtN (Dirichlet-to-Neumann) artiﬁcial boundary condition in order to solve three-dimensional wave-structure interactions or wave motion over piecewise topographies numerically. This paper is concerned with another artiﬁcial boundary condition or so-called NtD (Neumann-to-Dirichlet) boundary condition in order to solve water wave diﬀraction and independent radiation by a buoyant body. A virtual cylindrical surface enclosing the ﬂoating body is chosen as a boundary on which an exact NtD map is analytically derived from a solution of the exterior subregion and then it is specified as a boundary condition in order to solve the interior problem. The present model shows good accuracy through the comparison with the DtN approach and suggests the escalated results for the eﬀects of heading angle of incident wave and draft of a buoyant chamfer box.